(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2025)
In today’s society, the workplace serves as a pivotal setting for analyzing gender inequalities and dynamics. Although strides have been made toward gender equality, women still encountersystemic obstacles that impede their career advancement and satisfaction. This chapter investigates the complex challenges and inequalities women face in the workplace, drawing on recent research and theoretical perspectives from gender studies. It addresses issues like the gender pay gap, the glass ceiling, and the lack of representation of women in leadership positions. Additionally, it discusses the prevalent culture of sexism and discrimination that persists, causing women’s contributions to be undervalued. Employing Acker’s theory of gendered organizations and the notion of the "double bind" faced by women in professional environments, this chapter scrutinizes the structural and cultural elements that sustain gender disparities. It further explores how challenges related to work-life balance and the ideal worker standard affect women’s career decisions and opportunities. Moreover, this chapter emphasizes innovative strategies and policies organizations can adopt to promote gender diversity and inclusivity, including flexible work arrangements, mentorship initiatives, gender sensitive training, and clear promotion and compensation practices. By melding insights from sociology, gender studies, and organizational psychology, this chapter provides an extensive overview of gender dynamics in the workplace. It concludes with a call to action for collective efforts from stakeholders- employers, policymakers, and individuals- to remove the barriers women face, fostering a work environment where all genders can thrive equally.